Performance modelling for transparent computing using stochastic Petri nets. (2016) - Xue, Chao; Lin, Chuang
Massive applications, large-scale and disparity of demands tend to be the main characteristics of information technology. Therefore, to define an efficient computing paradigm with high quality of service has become an urgent issue both in academia and industry. An effective approach named transparent computing paradigm is proposed to meet the demands, which leaves computation and storage in different places. This paper studies the performance evaluation of such computing paradigm. We propose the stochastic Petri net models of transparent computing, based on which mathematical analysis is provided. Furthermore, we compare transparent computing paradigm with some traditional computing paradigms, both quantitatively and qualitatively.